PENGARUH DEBT DEFAULT, KUALITAS AUDIT, KONDISI KEUANGAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Ganny Frido Setiawan, 07.05.52.0087; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2014)
The purpose of this study was to examine the effect of debt default, audit quality, financial condition, companyâs growth on going concern audit opinion. Population and sample in this study is manufacturing companies listed in Indonesia Stock Exchange (IDX) the period of 2009 to 2012 with a sample of 41 manufacturing companies. The sample with purposive sampling technique. The Method of analysis used in this study is logistic regression. The results of this research showed debt default affected significance with audit opinion going concern than audit quality, financial condition, companyâs growth variable not affected significance with audit opinion going concern.Keywords: debt default, audit quality, financial condition, companyâs growth, going concern opinion